1989
DOI: 10.1099/00221287-135-10-2723
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Analysis of the Bacillus subtilis 1604 Spore Germination Response

Abstract: Germination at 37 degrees C of spores of Bacillus subtilis 1604 in the L-alanine and potassium phosphate (ALA) and the glucose, fructose, L-asparagine, potassium chloride (GFAK) germinant systems was triggered following heat activation at 70 degrees C for 1 h. In these conditions, 50% of the spore population became committed to germinate after exposure for 10 min and 14 min to ALA and GFAK, respectively, at which time 38% and 30% losses of OD600 had taken place. Dipicolinic acid (DPA) release, loss of heat res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 15 publications
5
36
0
Order By: Relevance
“…This positive staining is observed at least 1 h before the phase-dark spore formation, which is the microscopic indication of germinating spores. A study showed that 3-4 min after the initiation of germination of B. subtilis 1,604 strain, production of ATP is detected (Venkatasubramanian and Johnstone 1989). Fluorescence monitoring of NADH and dosage of ATP in germinating spore of B. megaterium QM B1551 also support this conclusion (Sano et al 1988).…”
Section: All Three Strains Of Bacillus Spores Responded Similarly To mentioning
confidence: 86%
“…This positive staining is observed at least 1 h before the phase-dark spore formation, which is the microscopic indication of germinating spores. A study showed that 3-4 min after the initiation of germination of B. subtilis 1,604 strain, production of ATP is detected (Venkatasubramanian and Johnstone 1989). Fluorescence monitoring of NADH and dosage of ATP in germinating spore of B. megaterium QM B1551 also support this conclusion (Sano et al 1988).…”
Section: All Three Strains Of Bacillus Spores Responded Similarly To mentioning
confidence: 86%
“…Preparation of autolysin-containing fractions. Unless otherwise stated, autolysin-containing samples were prepared Prior to germination, cleaned, dormant spores at 5 mg/ml (wt/vol) were heat activated at 70°C for 60 min (37). Heatshocked spore suspensions were germinated at 5 mg/ml at 37°C with constant shaking in 1 mM L-alanine-100 p.g of chloramphenicol per ml-50 mM potassium phosphate buffer (pH 7.0).…”
Section: Methodsmentioning
confidence: 99%
“…Mutations in gerA are the only ones known to specifically block the ALA response without affecting the AGFK response. In contrast a complex set of germinants is required for the AGFK response, the response is inhibited by sodium azide (Venkatasubramanian & Johnstone, 1989) and mutants of gerB and gerK are specifically blocked in the response.…”
Section: Ala (+Glu +Fru)mentioning
confidence: 99%